clij/clijx-weka: 0.30.1.19 - Robert Haase (Zenodo, 2021)
New features in label classification:
MeanOfLaplacian
Deprecated:
Local mean/min/max/stddev features were removed from the suggestion/selection list in the label classifiers / label feature generators, but they continue to work. Consider switching the the LabelRegionWekaClassifier in clijx.
See also:
https://github.com/clij/clij2/releases/tag/2.2.0.19